2020
DOI: 10.3390/jfb11020027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modification with Helium Atmospheric-Pressure Plasma and Deep-Ultraviolet Light on Adhesive Shear Strength of Fiber-Reinforced Poly(ether-ether-ketone) Polymer

Abstract: We investigated the effect of helium atmospheric-pressure plasma (PL) and deep-ultraviolet (UV) light treatments on the adhesive properties of fiber-reinforced poly(ether-ether-ketone) polymer (PEEK). PEEK disks reinforced with carbon (CPEEK) or glass (GPEEK) fibers were polished, modified with PL and UV for 60 s, and the surface energy was calculated by measuring the contact angles. The disk surfaces were analyzed by X-ray photoemission spectroscopy. Shear bond strength testing was performed using a universal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The bonding area was defined as the surface area of the ends of a SUS304 rod. According to the International Organization for Standardization’s recommendation, specimens were prepared at 23 ± 2 °C and stored in water at 37 ± 1 °C for 24 ± 1 h [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding area was defined as the surface area of the ends of a SUS304 rod. According to the International Organization for Standardization’s recommendation, specimens were prepared at 23 ± 2 °C and stored in water at 37 ± 1 °C for 24 ± 1 h [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Shear bond strength tests were performed at a crosshead speed of 1.0 mm/min using a universal testing machine (Autograph AG-1000E, Shimadzu, Kyoto, Japan) to obtain the maximum load [ 27 , 28 ]. The shear bond strength (S; MPa) was calculated using the following formula: S = P/A, where P is the maximum load obtained from the test and A is the cross-sectional area of the SUS304 rod.…”
Section: Methodsmentioning
confidence: 99%
“…PEEK is proposed as a promising alternative material to zirconia because of its superior mechanical properties. PEEK is also significantly less abrasive than zirconia [36]. Figure 1 shows clinical photographs of fixed dental prostheses made of PEEK.…”
Section: Fixed Dental Prosthesesmentioning
confidence: 99%
“…Okwa et al treated fiber reinforced PEEK with He plasma, which significantly increased the surface energies and generated OH functional groups [36]. CFR-and GFR-PEEK also showed higher wettability than a control, resulting from the chemical bonding within the interface, after He plasma modification (CFR-PEEK, θ at 37.2 ± 2.6 • ; GFR-PEEK, θ at 37.3 ± 4.2 • vs. CFR-PEEK, θ at 88.6 ± 0.9 • ; GFR-PEEK, θ at 74.4 ± 3.0 • ) [36]. However, Schmidlin et al and others have reported that He plasma treatment fails to enhance the SBS of ceramic-filled PEEK [89].…”
Section: Plasma Treatmentmentioning
confidence: 99%
“…For example, the introduction of hydrophilic groups (i.e. -OH, -NH 2 ) can facilitate the adhesion and proliferation of osteoblasts on the modified surface of a PEEK bone implant [74,85].…”
Section: Plasma Immersion Ion Implantationmentioning
confidence: 99%